The Role of School Principals in Building a Collaborative Work Culture to Improve Teacher Performance at SDN Rejosari and SDN Curah Dukuh I, Kraton District, Pasuruan Regency - Yulian Devinta Romli; Suyanto Suyanto; M. Furqon Wahyudi (The Future of Education Journal, 2025)
The school principal plays a strategic role in improving educational quality through the development of a work culture that supports teacher professionalism. One work culture that has been shown to influence improvements in teacher performance is a collaborative work culture. This study aims to describe the role of the principal in building a collaborative work culture and to analyze its impact on teacher performance at SDN Rejosari and SDN Curah Dukuh I, Kraton District, Pasuruan Regency. This research employed a qualitative approach with a descriptive design. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the interactive model proposed by Miles and Huberman. The findings indicate that principals act as instructional leaders, facilitators, and motivators in encouraging teacher collaboration through the provision of professional discussion forums, continuous coaching, and the creation of a supportive work climate. The established collaborative work culture has a positive impact on improving teacher performance, particularly in lesson planning, implementation, and evaluation. This study confirms that strengthening a collaborative work culture through effective principal leadership is an important strategy for enhancing the performance of elementary school teachers.